Insights into CYP2B6-mediated drug-drug interactions - William D. Hedrich; Hazem E. Hassan; Hongbing Wang (Elsevier, 2016)
Mounting evidence demonstrates that CYP2B6 plays a much larger role in human drug metabolism than was previously believed. The discovery of multiple important substrates of CYP2B6 as well as polymorphic differences has sparked increasing interest in the genetic and xenobiotic factors contributing to the expression and function of the enzyme. The expression of CYP2B6 is regulated primarily by the xenobiotic receptors constitutive androstane receptor (CAR) and pregnane X receptor (PXR) in the liver. In addition to CYP2B6, these receptors also mediate the inductive expression of CYP3A4, and a number of important phase II enzymes and drug transporters. CYP2B6 has been demonstrated to play a role in the metabolism of 2%-10% of clinically used drugs including widely used antineoplastic agents cyclophosphamide and ifosfamide, anesthetics propofol and ketamine, synthetic opioids pethidine and methadone, and the antiretrovirals nevirapine and efavirenz, among others. Significant inter-individual variability in the expression and function of the human CYP2B6 gene exists and can result in altered clinical outcomes in patients receiving treatment with CYP2B6-substrate drugs. These variances arise from a number of sources including genetic polymorphism, and xenobiotic intervention. In this review, we will provide an overview of the key players in CYP2B6 expression and function and highlight recent advances made in assessing clinical ramifications of important CYP2B6-mediated drug-drug interactions.